Karakterisasi Karbon Baggase Teraktivasi dan Aplikasinya untuk Adsorpsi Logam Tembaga - Dahlia Rosma Indah; Safnowandi Safnowandi (Universitas Pendidikan Mandalika, 2019)
Bagasse is waste produced from the process of milking or extracting sugarcane stems. Baggase can be optimized in terms of use value and its function as an alternative technology, namely as an active carbon manufacturing material that can be used as a copper (Cu) adsorbent. This study discusses the functional baggase activated carbon group of phosphoric acid and nitric acid using Fourier Transform Infra Red (FTIR) and its application as a copper metal adsorbent in silver craft waste in Ungga Village, Praya, Central Lombok. The production of activated bagasse carbon consists of three stages, namely first dehydration by burning bagasse until it turns into carbon, the second carbonation is heating at 500ºC, carbon results are 100-200 mesh and third, activation by soaking 50 grams of carbon in 500 mL of 20% phosphoric acid and 20% nitric acid for 12 hours. After that the carbon is dried at 110ºC and finally heated at 500ºC for 1 hour. The bagasse carbon that has been made is put into 25 mL of waste water sample with a mass of 2 grams of adsorbent. Samples were then stirred at 30, 60, 90, 120 and 150 minutes contact time variations at a speed of 180 rpm using a batch system. The optimum contact time that is used to calculate the efficiency of copper metal content reduction is by calculating the difference in the metal content of copper metal before it is adsorbed and after it is adsorbed using activated carbon baggase. Concentrations of all copper metals were analyzed using Atomic Absorption Spectrophotometer (AAS). Identification using FTIR spectrophotometer shows that carbon baggase in this study contains functional groups C = O, C = C, C-C, N = O, C = N, C-OH, CH2 and C-H. From the research it was found that the copper metal content in the sample was 14.5710 ppm. The optimum contact time on copper metal adsorption is at 120 minutes contact time which results in optimum adsorption efficiency on copper metal that is 84.88%. Activated carbon baggase is an effective adsorbent to reduce levels of copper metal in silver craft waste.